Factors influencing apical debris extrusion during endodontic treatment - A review of the literature - Predin Djuric, Natasa; Van der Vyver, Peet J; Vorster, Martin; Vally, Zunaid I (South African Dental Journal, 2021)
The primary cause of a periapical inflammatory lesion is intra-radicular microbial infection. Prevention and elimination of apical periodontitis is achieved through successful endodontic treatment. Endodontic treatment is designed to maintain and restore the health of the periapical tissues and prevent periapical disease. It may be defined as the combination of mechanical instrumentation of the root canal system with bactericidal irrigation and obturation with an inert material. Technically, the goal of instrumentation and irrigation is to debride and entirely remove infected tissue debris from the root canal system and create a uniform conical shape that allows medicament delivery and adequate obturation. Microbiologically, the goal of instrumentation and irrigation is to eliminate micro-organisms, reduce their survival in the root canal system and neutralise any antigenic potential of the microbial components remaining in the canal.